LINKING INNOVATION CAPABILITY TO BUSINESS PERFORMANCE OF BICOLANA ENTREPRENEURS - Caning, Ma. Cresilda M. (Animo Repository, 2022)
If innovation is perceived as important to business growth then it is imperative for businesses to foster the capability to innovate. With this premise, this research explored the relationship between the different aspects of innovation capability to an enterprise’s strategic capability, as indicated by their marketing and organizational innovation practices, and of strategic capability to the business performance of the Bicolana pili processors. The RBV framework was used as an anchor framework in examining the relationship of the different aspects of innovation capability to the strategic capability of 92 Bicolana pili processors and eventually to their financial and operational performances. Using the sequential mixed method, the research found that of the different innovation capability aspect, it was only the participatory leadership culture that showed a positive significant relationship to both marketing and organizational innovation capability. Further, result of the stepwise regression analysis revealed that marketing innovation has significant relationship to increase in profit, innovation in product and services, and innovation in process. For the organizational innovation, results showed that it has significant relationship to adoption of new business practice, an operational performance indicator. Considering the result of the study, the research recommends that further study on other factors not considered in the model that can mediate or influence the relationship between the different variables. Similarly, given the geographical context of the study, there might be other cultural variables, not examined but can influence conditions within the organization to be studied. Also, further studies on the influence of the external environment on the performance of the business can be done since this study focuses on the internal environment of the business. Finally, the study suggests a new innovation capability model with people-centric leadership culture replacing participatory leadership culture. The new construct is characterized by a people-centric leadership and open communication and is posited as a determinant of both marketing and organizational innovation capability. It is suggested that the explanatory power of the proposed innovation capability model can be improved by considering other factors such as the network the women have established and the enabling support given by the government and other institutions in marketing and R & D. It is also suggested that the government should continue providing the necessary marketing support, i.e., design and packaging to entrepreneurs and organizational support such as the provision of the necessary equipment, especially to the start-ups to enhance the innovativeness and ensure the business performance and sustainability of rural-based women entrepreneurs.